Critical Making in the Age of AI - Johnson, Emily; Salter, Anastasia (Amherst College Press, 2025)
Critical Making in the Age of AI invites students, teachers, learners, and digital humanists to explore making as scholarship. Inspired by the craft traditions of textile arts, this book combines a survey of forms of alternative scholarly communication—such as comics, GIFs, maps, games, and generative AI—and a pattern book, where patterns serve as starting points that makers can reimagine and remix. Firmly grounded in the humanities and utilizing free tools and platforms (including Twine, Voyant, and Tracery) wherever possible, this engaging and accessible guide to digital methods introduces and puts into practice concepts that are essential to preparing students to navigate a changing landscape of media and information without investing in proprietary software, dedicated lab space, or expensive creative tools. The book’s eight patterns are especially appropriate for those just beginning to explore digital scholarly methods, and one goal of Critical Making in the Age of AI is to provide structure for work that is both meaningful and achievable with limited resources and time. By centering critical making through a design-justice and feminist lens, the coauthors model how inclusive and expansive approaches to making in research and teaching are vital to shaping the humanities of the future.